2022
DOI: 10.23917/jisel.v5i1.17139
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Halal Label in Halal Food Buying Decisions

Abstract: The current development of the halal industry in the world has experienced a very significant increase to attract the attention of various groups. Trend indicators from the halal business can be seen in seven industrial sectors that continue to show an increase, including Islamic financial services, Halal food and beverages, Halal tourism, fashion, halal media and recreation, and well as halal pharmaceuticals and cosmetics. This study will raise the halal label on halal food and beverages in Indonesia. The qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…Muslim tourists believe that halal food that has been certified will be guaranteed quality, safety, and cleanliness. Novelty and taste are also motivations for tourists to taste halal food; consuming halal food can be a positive emotional experience Muslim tourists feel, which will later become good memories [78].. Labeling must be done because of the increasing awareness of halal, a lifestyle for the Muslim community [80].…”
Section: Further Research Discussion and Opportunitiesmentioning
confidence: 99%
“…Muslim tourists believe that halal food that has been certified will be guaranteed quality, safety, and cleanliness. Novelty and taste are also motivations for tourists to taste halal food; consuming halal food can be a positive emotional experience Muslim tourists feel, which will later become good memories [78].. Labeling must be done because of the increasing awareness of halal, a lifestyle for the Muslim community [80].…”
Section: Further Research Discussion and Opportunitiesmentioning
confidence: 99%
“…Vizano et al ( 2021) also showed that intention influences the decision to buy halal food. The decision to buy halal food is heavily influenced by purchase intentions (Millatina et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…First, avoid what fiqh scholars say is forbidden or haram. This first level can be identified one way by paying attention to the product's halal status based on the halal certificate issued by the Indonesian Ulema Council (Indonesian: Majelis Ulama Indonesia), for example by looking at the halal logo or attribute, images and writing on the product packaging, as well as the shape of the packaging [35].…”
Section: Content Of Islamic Financial Literacy Education From Al-ghaz...mentioning
confidence: 99%